Reconfiguring Distribution Grids (Bulletin of the South Ural State University series "Power Engineering", 2021)
Optimizing the grid structure becomes necessary in case of post-emergency power restoration or when overloaded. In normal operation, distribution grid parameters are adjusted to reduce the overload and the electricity losses; reconfiguration is not considered. The grid topology is reconfigurable by solving the optimization problem by the branch-and-bound algorithm subject to keeping the parameters within their acceptable limits in the context of line resistance, electricity losses, and power flows for all possible grid layouts. Simulation of a 10-kV distribution grid with four power centers shows that reconfiguring reduces power consumption by 2.9% and the inline active power losses by 256 kW. In this case study, reconfiguring has helped keep the voltage within the acceptable range while not overloading the lines. This study shows the proposed approach is suitable for dynamic grid reconfiguration as a way to reduce the overload and the electricity losses; at the same time, the approach does not require calculating nonlinear steady-state equations for each possible grid topology.